A Novel DNA Aptamer Probe Recognizing Castration Resistant Prostate Cancer in vitro and in vivo Based on Cell-SELEX - Zhong J; Liu D; Yang Q; Ding J; Chen X (Dove Medical Press, 2024)
Jinman Zhong,1 Duoduo Liu,1 Quanxin Yang,1 Jianke Ding,2 Xin Chen1 1Department of Radiology, The Second Affiliated Hospital, Xi' an Jiaotong University, Xi'an, Shaanxi Province, 710004, People's Republic of China; 2Department of Plastic and Reconstructive Surgery, Xijing Hospital, Fourth Military Medical University, Xi'an, Shaanxi Province, 710032, People's Republic of ChinaCorrespondence: Xin Chen, Department of Radiology, The Second Affiliated Hospital, Xi' an Jiaotong University, 157 Xiwu Road, Xi'an, Shaanxi Province, 710004, People's Republic of China, Email chen_x129@163.com Jianke Ding, Department of Plastic and Reconstructive Surgery, Xijing Hospital, Fourth Military Medical University, 127 Changle West Road, Xi'an, Shaanxi Province, 710032, People's Republic of China, Email dingjianke@qq.comBackground: Early recognition of castration-resistant state is of significance for timely adjustment of treatment regimens and improvement of prognosis.Purpose: This study aims to screen new aptamers CRda8 and CRda21 which recognize castration resistant prostate cancer (CRPC) cells with high affinity and specificity by SELEX technology.Methods: The enrichment of specific aptamer candidates was monitored by flow cytometric analysis. The affinity and specificity of aptamer candidates were evaluated by flow cytometry and immunofluorescence assay. MR imaging of CRda21-conjugated polyethylene glycol (PEG)-Fe3O4 nanoparticles to CRPC was further explored in vivo.Results: Both aptamers showed high specificity to target cells with dissociation constants in the nanomolar range, and did not recognize other tested cells. The staining of clinical tissue sections with fluorescent dye labeled aptamers showed that sections from CRPC exhibited stronger fluorescence while sections from benign prostatic hyperplasia and androgen dependent prostate cancer did not exhibit notable fluorescence. In vivo MRI demonstrated that CRda21-conjugated PEG-Fe3O4 had good affinity to CRPC and produced strong T2WI signal intensity reduction distinguished from peritumoral tissue.Conclusion: The high affinity and specificity of CRda8 and CRda21 make the aptamer hold potential for early recognition of castration-resistant state and diagnosis of CRPC at the cellular level.Keywords: aptamer, Cell-SELEX, MRI, castration resistant prostate cancer, androgen dependent prostate cancer